System for evaluation of cognitive performance under the emotional stressors - Ćosić, Krešimir (Array, 2014)
It is well known that emotional stressors may have adverse effects on cognitive-motor performance. The system for evaluation of cognitive-emotional interactions, described in this paper, is based on real-time interplay between a selected cognitive task and selected emotional stressors, and may facilitate insight into an individual’s variation of cognitive and emotional parameters and variables. To illustrate the effects of emotional distraction on cognitive-motor performance, specific cognitive-motor test has been designed and combined with aversive highly arousing emotional distractions, including pictures, sounds, acoustic startle impulses and air blasts, while measuring multimodal physiological, vocal, facial, and electroencephalography (EEG) responses. Preliminary two-phase experimental paradigm has been conducted: Phase 1 – cognitive- motor performance testing with neutral distractions, and Phase 2 – cognitive-motor performance testing under aversive highly arousing emotional distractions. Aversive emotional distractions delivered in Phase 2 transiently reduced cognitive-motor performance and produced stronger skin conductance changes in comparison to Phase 1 neutral distractions.